2015
DOI: 10.3402/ijch.v74.27963
|View full text |Cite
|
Sign up to set email alerts
|

Adequate vitamin D levels in a Swedish population living above latitude 63°N: The 2009 Northern Sweden MONICA study

Abstract: BackgroundEven though vitamin D is mainly produced by exposure to sunlight, little is known regarding vitamin D levels in populations living in sub-Arctic areas with little or no daylight during winter.ObjectiveWe describe distributions of vitamin D3 and the prevalence of adequate levels in a population living above 63°N.DesignWe sampled 1,622 randomly selected subjects, aged 25–74 years, between January and May, 2009, as part of the Northern Sweden MONICA study (69.2% participation rate). By using HPLC, 25(OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 41 publications
8
29
0
1
Order By: Relevance
“…Thus, improvement in diet, decreased BMI, increased physical activity, quitting smoking, and increased alcohol consumption were independently associated with an increased 25-OH-D during a 5-year period. Except for the association between changes in intake of alcohol, dietary and smoking habits, and vitamin D status, these findings were supported by additional analyses In line with previous studies, vitamin D status was generally higher in women than men [26,27].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, improvement in diet, decreased BMI, increased physical activity, quitting smoking, and increased alcohol consumption were independently associated with an increased 25-OH-D during a 5-year period. Except for the association between changes in intake of alcohol, dietary and smoking habits, and vitamin D status, these findings were supported by additional analyses In line with previous studies, vitamin D status was generally higher in women than men [26,27].…”
Section: Discussionsupporting
confidence: 88%
“…The limitations of the study include the lack of repeated measurements of plasma 25(OH)D and dietary vitamin D intakes, the lack of information on sun exposure as a covariate, and the inclusion of men only. In this overall healthy cohort, there were very few participants with low concentrations of 25(OH)D; however, this factor is in line with previous studies in community-dwelling people (58,59) in Sweden. Future studies may want to focus on a population in whom vitamin D deficiency is more prevalent.…”
Section: Discussionsupporting
confidence: 77%
“…The present study confirmed previous results from studies of the seasonal variation of vitamin D in Scandinavia [9][10][11] as we found 42% higher 25(OH)D level in summer compared to winter. Even the PTH level showed a difference between summer and winter with 7% lower PTH level in summer compared to winter, also in accordance with previous reports [1].…”
Section: Discussionsupporting
confidence: 96%